Qigong versus exercise therapy for chronic low back pain in adults – A randomized controlled non‐inferiority trial. (5th June 2014) - Blödt, S.; Pach, D.; Kaster, T.; Lüdtke, R.; Icke, K.; Reisshauer, A.; Witt, C.M.
Abstract Background The value of qigong in the treatment of chronic low back pain is unclear. In a randomized controlled trial, we evaluated whether qigong is non‐inferior to exercise therapy in patients with chronic low back pain. Methods German outpatients (aged 46.7 ± 10.4) with chronic low back pain [mean visual analogue scale (VAS), 53.9 ± 12.5 mm] were enrolled and randomly allocated in a 1:1 ratio to receive either qigong (64 patients, 12 sessions with 1 × 90 min/week over 3 months) or exercise therapy (63 patients, 12 sessions 1 × 60 min/week). The primary outcome measure was the average pain intensity over the last 7 days on a VAS (0–100 mm, 0 = no pain, 100 = worst imaginable pain, non‐inferiority margin = 5 mm) after 3 months. Follow‐up was measured after 6 and 12 months. Results The mean adjusted low back pain intensity after 3 months was 34.8 mm [95% confidence interval (CI) 29.5; 40.2] in the qigong group and 33.1 mm (95% CI 27.7; 38.4) in the exercise group. Non‐inferiority of the qigong group compared with the exercise group failed to show statistical significance (p = 0.204). In both groups, 10 patients reported suspected adverse reactions (e.g., muscle soreness, dizziness, pain) the total number was comparable in both groups (qigong n = 40, exercise n = 44). Conclusions Qigong was not proven to be non‐inferior to exercise therapy in the treatment of chronic low back pain. Its role in the prevention of chronic low back pain might be addressed in further studies.